Mazahib At-Tafsir: Konstruksi Epistemologis dan Peta Aliran Dalam Tradisi Penafsiran Al-Qur'an - Rizki Rahmadani; Lasmiati Radiah; Akhmad Dasuki (JOURNAL SAINS STUDENT RESEARCH, 2026)
The interpretive plurality in the study of the Qur'an reflects fundamental differences in the way of answering fundamental questions of hermeneutics that have a direct impact on the law, ethics, and social life of the Muslim community. This research aims to identify the main streams of interpretation along with their epistemological and methodological characteristics, analyze the theoretical and intellectual genealogy foundations of each stream, examine the tensions between streams in their historical development, and formulate an integrative framework for the development of contemporary interpretation methodologies. The method used is qualitative with a library research approach and data analysis through three stages: descriptive-analytical content analysis, comparative analysis, and integrative synthesis. This study found five main schools of mazahib al-tafsir with distinctive epistemological characteristics, namely al-tafsir bil-ma'tsur which relies on the authority of transmission, al-tafsir bil-ra'yi which activates rational ijtihad, al-tafsir al-ishari which prioritizes the esoteric-spiritual dimension, al-tafsir al-'ilmi which connects the text with the findings of modern science, and al-tafsir al-maudhu'i which prioritizes thematic coherence. The dialectical tension between flows is patterned on two main axes, namely between textual authority and contextual relevance, and between transmission and transformation. This research has implications for the need for an integrative approach that recognizes the legitimacy of each school according to its function while establishing a clear methodological hierarchy in the study of interpretation